Hectorite-CTAB–alginate composite beads for water treatment: kinetic, isothermal and thermodynamic studies. Issue 2 (3rd January 2023) - Asranudin,; Holilah,; Purnomo, Adi Setyo; Bahruji, Hasliza; Allouss, Dalia; El Alaoui-Elbalrhiti, Ilias; Subagyo, Riki; Rohmah, Alya Awinatul; Prasetyoko, Didik
Abstract : Encapsulation of hectorite-modified CTAB with Ca-alginate formed reusable adsorbent beads for wastewater treatment. Abstract : Encapsulation of hectorite-modified CTAB with Ca-alginate formed reusable adsorbent beads for wastewater treatment. The thermogravimetric analysis (TGA) investigation indicated excellent thermal stability results for BHec-40 compared to Hec-40. Although the mesoporous surface area of BHec-40 decreased to 79.74 m 2 g −1 compared to 224.21 m 2 g −1 for Hec-40, the hectorite-CTAB–alginate beads showed high adsorption capacity and stability for methyl orange (MO) adsorption with more than 60% removal after five adsorption–desorption cycles. The influence of pH (3–11), temperature (30, 40, and 50 °C), initial concentration (50–400 mg L −1 ), and contact time were studied to obtain the kinetics and thermodynamics of adsorption. The outcomes revealed a maximum monolayer adsorption capacity of 117.71 mg g −1 for BHec-40. The kinetics of adsorption demonstrated the suitability of using the pseudo-first-order kinetic model, while the equilibrium adsorption data follows the Langmuir isotherm. Thermodynamic analysis indicates physisorption of MO onto BHec-40. BHec-40 improves the reusability as an adsorbent for the removal of anionic dyes from aqueous media.